THE MEANING OF THE NIQAB IN SOCIAL INTERACTION STUDENTS IN SERANG CITY - Sidik, Irfan Hakim; Malik, Abdul; Putri, Liza Diniarizky; Annisarizki, Annisarizki (ASPIRATION Journal, 2023)
The Niqab is clothing used to cover the face, at least to cover the nose and mouth. This research focuses on aspects of communication, both interpersonal and interpersonal communication, as well as communication events experienced by female students who wear the Niqab on campus and in other public spaces. This research also tries to reveal their experiences of mingling amid a heterogeneous society, especially female students in the city of Serang. This research uses a qualitative approach with phenomenological research methods with four female informants. The theories used are social action theory and Alfred Shcutz's phenomenological theory as research references. In this research, it can be concluded that the symbolic meaning is the meaning of the Niqab for female students in the city of Serang who use it in their daily lives. In this research, this research aims to understand the symbolic meaning used by subjective actors for reasons including self-protection. Then there is the motive of using the Niqab as a form of social action. The motive itself has three parts, namely past, present, and future motives. Factors that encourage these motives include: revealing identity, habits, and image formation.